A new family of Mn-based perovskite (La1-xYxMnO3) with improved oxygen electrocatalytic activity for metal-air batteries. (1st July 2018) - Miao, He; Wang, Zhouhang; Wang, Qin; Sun, Shanshan; Xue, Yejian; Wang, Fu; Zhao, Jiapei; Liu, Zhaoping; Yuan, Jinliang
Abstract: The sluggish reaction kinetics occurring at the cathodes limits the performances of the metal-air batteries. Therefore, developing the oxygen electrocatalysts which can accelerate oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is a critical issue. Mn-based perovskite has drawn extensive interests though their ORR and OER catalytic activity still needs to be improved. In this work, a new family of Mn-based perovskite (La1-x Yx MnO3, LYM) is developed which demonstrates an improved ORR and OER catalytic activity compared with the representative strontium-doped Mn-based perovskite (LSM). For La0.9 Y0.1 MnO3 (LYM-10), the onset potential and half-wave potential during ORR can reach 0.909 V and 0.750 V (vs. RHE), respectively, which are more positive than those of LSM reported in most of the recent reports. Furthermore, LYM-10 also shows a better OER catalytic activity than La0.7 Sr0.3 MnO3 (LSM-30). In addition to its good bifunctional property, LYM-10 also achieves the superior durability compared with Pt/C during ORR, and the current retention of LYM-10 is as high as 97.3% after 43000 s. Using LYM-10 as the cathode catalyst, the alunimum-air battery can reach the maximum power density of 266 mW/cm 2, and zinc-air battery can obtain low charge-discharge overpotential and the good cycling stability. Highlights: A new family of Mn-based perovskite (LYM) is developed. LYM-10 demonstrates an improved ORR and OER catalytic activity compared with LSM. LYM-10 also achieves the superior durability compared with Pt/C during ORR. Zinc-air battery can obtain low charge-discharge overpotential and good stability using LYM-10.